Azithromycin removal from water via adsorption on drinking water sludge-derived materials: Kinetics and isotherms studies. - Camilo C Castro-Jiménez; Julio C Saldarriaga-Molina; Edwin F García; Ricardo A Torres-Palma; Nancy Acelas (PLoS ONE)
In this study, we utilized drinking water treatment sludge (WTS) to produce adsorbents through the drying and calcination process. These adsorbents were then evaluated for their ability to remove azithromycin (AZT) from aqueous solutions. The L-500 adsorbent, derived from the calcination (at 500°C) of WTS generated under conditions of low turbidity in the drinking water treatment plant, presented an increase in the specific surface area from 70.745 to 95.471 m2 g-1 and in the total pore volume from 0.154 to 0.211 cm3 g-1, which resulted in a significant AZT removal efficiency of 65% in distilled water after 60 min of treatment. In synthetic wastewater, the rate of AZT removal increased to 80%, in comparison, in a real effluent of a municipal wastewater treatment plant, an AZT removal of 56% was obtained. Kinetic studies revealed that the experimental data followed the pseudo-second-order model (R2: 0.993-0.999, APE: 0.07-1.30%, and Δq: 0.10-2.14%) suggesting that chemisorption is the limiting step in the adsorption using L-500. This finding aligns with FTIR analysis, which indicates that adsorption mechanisms involve π-π stacking, hydrogen bonding, and electrostatic interactions. The equilibrium data were analyzed using the nonlinear Langmuir, Freundlich, and Langmuir-Freundlich isotherms. The Langmuir-Freundlich model presented the best fitting (R2: 0.93, APE: 2.22%, and Δq: 0.06%) revealing numerous interactions and adsorption energies between AZT and L-500. This adsorbent showed a reduction of 19% in its AZT removal after four consecutive reuse cycles. In line with the circular economy principles, our study presents an interesting prospect for the reuse and valorization of WTS. This approach not only offers an effective adsorbent for AZT removal from water but also represents a significant step forward in advancing sustainable water treatment solutions within the framework of the circular economy.